Screening of Red Rice (Oryza sativa L.) Landraces for Drought Tolerance at Early Stages Using PEG 6000 - Siti Fatimah; Achmad Amzeri; Mohammad Syafii; Yuzy Purwaningsih (AGRIVITA, Journal of Agricultural Science, 2023)
Despite being one of the most important staple food consumed by more than half of the world population, the development of red rice still lacks behind the regular white rice. In Madura, most farmers still use their local landraces with red pericarp. Since most of the growing season is dependent on rainfall, those landraces are expected to provide some useful genes related to drought tolerance. This research aimed to select drought-tolerant accessions candidates of red rice derived from pure lines selection at early stages using PEG 6000. A randomized complete block design was used with two factors and three replications, the first factor was red rice genotype and the second factor was two levels of PEG 6000 concentration (0% and 25%). The results showed that there were different responses in all genotypes used in terms of their responses to PEG 6000 screening. Seedling length, seminal root length, shoot length, seminal root dry weight, and shoot dry weight were reduced by the application of PEG 6000 compared to non-PEG 6000 media. Two genotypes had a better response to PEG 6000 treatment compared to check tolerant (Salumpikit), and these are expected to become a valuable resources for further breeding activities.